1997
DOI: 10.1177/1358863x9700200207
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen and Cardiovascular Risk

Abstract: The hypothesis that fibrinogen is closely related to cardiovascular risk has been strengthened through the results of various lines of research, which this review will aim to unravel. Several prospective epidemiological studies convincingly show elevated fibrinogen to represent a major, independent cardiovascular risk factor. Cross-sectional studies strongly associate fibrinogen and conventional cardiovascular risk factors. Clinical cohort studies demonstrate that increased fibrinogen is also a risk factor for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0
9

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(46 citation statements)
references
References 144 publications
2
35
0
9
Order By: Relevance
“…Some studies in apparently healthy subjects have reported increased incidences of cardiovascular diseases in patients with elevated levels of inflammation markers [20][21][22].…”
Section: Discussionmentioning
confidence: 98%
“…Some studies in apparently healthy subjects have reported increased incidences of cardiovascular diseases in patients with elevated levels of inflammation markers [20][21][22].…”
Section: Discussionmentioning
confidence: 98%
“…However, fenofibrate has an additional beneficial effect on fibrinogen levels that other agents do not have. Serum fibrinogen is directly correlated with plasma viscosity [6], which is also a cardiovascular risk factor [39]. As previously mentioned, fibrates exert their major effects via PPAR-/.…”
Section: Discussionmentioning
confidence: 98%
“…22 Fibrinogen concentration has also been associated with cardiovascular risk; in the present study we did identify a positive correlation between d f and fibrinogen concentration but fibrinogen was not significantly raised when comparing obstructive and unobstructive CAD. 23 This suggests that while age is associated with advanced CAD, age itself is not the driving force behind the development of abnormal clot formation.…”
Section: Discussionmentioning
confidence: 99%